The effect of slaughter age on the bacterial number, pH and carcass weight loss of Japanese quails stored at 4°C for 14 days. - Jamaludin, M. H.; Aisyah, W. S. K.; Shazani Sarijan; Amin, M. R. (2013)
The main objective of this study was to evaluate the effect of slaughtering age on the bacterial profile, pH, and carcass loss of dressed Japanese quails (Coturnix japonica) stored aerobically at 4°C over a period of 14 days. Quails at 3 weeks (n=15), 9 weeks (n=15) and 36 weeks (n=15) were slaughtered and divided into triplicate samples at storage time of 0, 3, 7, 10 and 14 days. There was no difference (P>0.05) in total aerobic bacteria, pH and carcass weight loss percentage between the birds of different slaughtering age at the respective sampling days. Except for quail dressed weight, sampling age did not affect bacterial numbers, pH and carcass weight at the respective sampling day during the aerobic chilled storage of Japanese quails. Future studies should consider other meat quality parameters to include the various biochemical and physical changes of carcass during storage.